استعمال نظام محاسبة المسؤولية في تقويم اداء مراكز الربح: بالشركة العامة للصناعات الجلدية (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Use the accounting system of responsibility in assessing the performance of the company profit centers of the leather industry Given the importance of the profit centers of the General Company for Leather Industries, where a circle of activity that is accountable responsible for them (the director) about what is happening with costs and achieve revenues other words, the profit center is the beginning of an independent company with revenues and costs contribute to achieving the objectives of the company as a whole, which is to achieve profits, which means the comprehensive work of the centers of the need to evaluate its performance permanent depending on the conversion rates of the Interior. It was relied on the company's production schedules for the period from 2008 through 2010 to determine the contribution of each of the profit centers in profits using the internal conversion rates Where the conversion price for the center of the seller is the market price and the price of conversion of the center of Jupiter is the variable cost we recommend using the General Company for Leather Industries sample two prices for the transfer to it is compatible with both the seller and the buyer and thus encourage officials to serve the goals of the company and this requires a degree of flexibility in the selection method appropriate.